La diagnosi psichiatrica: il ruolo del medico di medicina generale - Fagioli, Marcella; Fagioli, Luca (Il sogno della farfalla, 2010)
International scientific literature tells us that 73% of first episode psychotic cases are preceded by a period, which averages from 2 to 4 years, in which it is possible to detect a number of signs of unease and difficulty before psychotic symptoms emerge more evidently. The prodromic manifestations and psychotic onset can be positioned on the border between maturation processes and pathology, an area which is often neglected by Psychiatric Services which are for organizational and theoretical reasons oriented towards full-blown pathologies, in an acute or chronic phase. Given this situation the role of general practitioners appears fundamental, being in the position where they have day-to-day contact with their patients and their respective families. If adequately informed about the prodromic manifestations of juvenile psychosis, general practitioners can report these disturbances to the special services, make families more sensitive to these problems, collaborate and constitute a liaison between psychiatry and family and therefore facilitate an early preventative and/or therapeutic intervention, which will prove more effective the earlier it occurs. This would allow a real and proper preventative strategy to take place, which is the most valid instrument (as authoritative research has confirmed) to prevent evolution towards a more serious psychosis.